Engineering considerations for optical diagnostics of European DEMO - Katona, I.; Dunai, D. (Fusion engineering and design, 2025)
Optical diagnostics measurements were identified as necessary for plasma control in the initial concept for the plasma diagnostic and control (D&C) system of European DEMO. The protection of the first mirror is identified as a critical subject for future large sized fusion devices. Radio Frequency Plasma Discharge mirror cleaning solutions proposed for ITER have been discarded for fusion power plant environment. Erosion and deposition processes can be mitigated by neutral gas between the aperture and the front mirror. Currently 3 optical diagnostics are being developed for EU-DEMO. The Divertor Monitoring Diagnostic had the highest priority thus that was selected for conceptual development. Three optomechanical layout configurations were analyzed, with the optimal candidate further refined for improved integration and performance. The design emphasized the optical duct geometry, revealing that a shorter duct simplifies mechanical integration. Preliminary Monte Carlo N-Particle (MCNP) neutronics simulations estimated the diagnostic module's nuclear load, providing key insights for further refinement. This iterative workflow enables systematic optimization of the optical and mechanical structure to meet stakeholder requirements, yielding a robust, integrated diagnostic module design. The methodology offers a transferable framework for other optical diagnostics under development for EU-DEMO and future fusion power plants.